Leveraging Waste Recycling as a Gateway to a Green Economy in Nigeria - Nathaniel Oluwaseun Ogunseye; Omololu David Ogunseye; Abiodun Olanrewaju Ogunseye; Samuel Osayamen Tongo; Johnson Olarinde Oladesu; Michael Abiodun Oyinloye; Festus Osarumwense Uzzi (The Journal of Indonesia Sustainable Development Planning, 2024)
The call for a transition to a green economy has been a recurring issue in Nigeria for over a decade. However, there was limited focus on the relationship between waste recycling and the green economy in previous studies. This study explores the nexus between waste recycling and the green economy, examining how waste recycling can be leveraged to foster a green economy in Nigeria. A descriptive qualitative approach was used, and relevant literature from secondary data sources and context were analyzed. The results indicate that waste recycling has not been fully embraced in Nigeria, especially at the household level. Therefore, waste recycling is primarily driven by the informal sector and entrepreneurs. Furthermore, the study reveals the diverse opportunities available through implementing a green economy. It recommends a green economy policy that promotes equity, economic incentives for household waste recycling, and support for entrepreneurs interested in partnering with the government.